2005
DOI: 10.1099/jmm.0.45812-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of bacteria and host factors in an outbreak situation of antibiotic-associated diarrhoea

Abstract: Antibiotic-associated diarrhoea (AAD) represents a clinical entity leading to prolonged hospital stays and diagnostic and therapeutic procedures, and results in additional costs. The aim of the present study was to assess the prevalence and characteristics of different bacteria in stools of patients with AAD. The reliability of diagnostic procedures under routine conditions was evaluated. Host factors were also analysed. From June 2002 to April 2003 89 cases of diarrhoea were reported at a hospital unit for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 28 publications
1
22
0
4
Order By: Relevance
“…In this study S. aureus was the only identified pathogenic micro-organism to cause AAD in 47 patients and the presence of staphylococcal enterotoxin A was strongly associated with the development of diarrhea. A German study reported intestinal carriage of S. aureus, in the absence of C. difficile in 8% of patients with AAD [69]. Compelling evidence for the etiological role of MRSA in AAD was provided by excluding the involvement of C. difficile, numerous other bacterial pathogens and parasites, but also several enteric viruses in 11 patients with enterotoxin-producing MRSA intestinal carriage [70].…”
Section: Potential Role Of S Aureus In Intestinal Diseasementioning
confidence: 99%
“…In this study S. aureus was the only identified pathogenic micro-organism to cause AAD in 47 patients and the presence of staphylococcal enterotoxin A was strongly associated with the development of diarrhea. A German study reported intestinal carriage of S. aureus, in the absence of C. difficile in 8% of patients with AAD [69]. Compelling evidence for the etiological role of MRSA in AAD was provided by excluding the involvement of C. difficile, numerous other bacterial pathogens and parasites, but also several enteric viruses in 11 patients with enterotoxin-producing MRSA intestinal carriage [70].…”
Section: Potential Role Of S Aureus In Intestinal Diseasementioning
confidence: 99%
“…In the diagnosis and typing of C. difficile, culture techniques are seldom used, which may result in underestimating the detection of this organism (19). Instead, several immunological (2,8,65,66) and PCR-based methods, including those directed at identifying and in some cases quantifying the tcdA and tcdB genes and the cdtA and cdtB genes, encoding TcdA and TcdB or CDT, respectively, in stool samples, have been described (6,22,38,52).…”
mentioning
confidence: 99%
“…This form of food poisoning is severe: 10% of the affected individuals require a visit or an admission to the hospital (1)(2)(3)(4)(5)(6). Staphylococcal enterotoxin food poisoning leads to inflammatory changes throughout the gastrointestinal (GI) tract with severe lesions in the jejunum and ileum (7)(8)(9)(10).…”
mentioning
confidence: 99%